Comparative Performance of Sentinel-2 and Landsat-9 Data for Raw Materials’ Exploration Onshore and in Coastal Areas - Morgana Carvalho; Joana Cardoso-Fernandes; Francisco Javier González; Ana Claudia Teodoro (Remote Sensing)
The demand for Critical Raw Materials (CRM) is increasing due to the need to decarbonize economies and transition to a sustainable low-carbon future achieving climate goals. To address this, the European Union is investing in the discovery of new mineral deposits within its territory. The S34I project (Secure and Sustainable Supply of Raw Materials for EU Industry) is developing Earth observation (EO) methods to support this goal. This study compares the performance of two satellites, Sentinel-2 and Landsat-9, for mineral exploration in two geologically distinct areas in northern Spain. The first area, Ria de Vigo, contains marine placer deposits of heavy minerals, while the second, Aramo, hosts Co-Ni epithermal deposits. These sites provide exceptional case studies to improve EO-based methods for CRM exploration onshore and coastal regions, focusing on deposits often overlooked in remote sensing studies. Standard remote sensing methods such as RGB combinations, Principal Component Analysis (PCA), and band ratios were adapted and compared for both satellites. The results showed similar performance in the Ria de Vigo area, but Sentinel-2 performed better in Aramo, identifying a higher number of zones of mineral alterations. The study highlights the advantages of Sentinel-2’s higher spatial resolution, especially for mapping smaller or more scattered mineral deposits. These findings suggest that Sentinel-2 could play a larger role in mineral exploration. This research provides valuable insights into using EO data for diverse CRM deposits.